The Role of Thematic Videos in Teaching Basic Skills to Young Learners: Benefits and Challenges - Maghfiroh, Suanah Sevira; Isnawati, Uzlifatul Masruroh (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study investigates the role of thematic videos in teaching basic English skills—listening, speaking, reading, and writing—to early childhood students at the elementary level. Guided by constructivist and multimodal learning theories, the study examines the pedagogical benefits and practical challenges of video-based learning. The researchers employed a library research method. Data collection began by identifying scholarly sources from trusted databases, including Google Scholar, ERIC, ScienceDirect, and ResearchGate. Keywords such as thematic videos, young learners, multimodal learning, and basic English skills were used to retrieve relevant studies. The findings indicate that thematic videos, when carefully selected and aligned with learning objectives, can improve vocabulary retention, pronunciation accuracy, and contextual understanding. Thematic videos also foster student motivation, positive attitudes, and collaborative engagement. However, challenges arise in maintaining attention, ensuring language comprehension, and addressing teachers limited digital access and media literacy. Excessive exposure to visual stimuli without guided scaffolding can further limit productive language use. This study concluded that thematic videos serve as an engaging and accessible medium for supporting basic English language skills. Their effectiveness depends on interactive integration, teacher mediation, and the use of culturally relevant materials.